2014
DOI: 10.1016/j.jaac.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parental Mood on Reports of Their Children’s Psychopathology

Abstract: Objective In this study, we aim to assess whether current mood state (depressed or manic/hypomanic) among parents with a mood disorder affects their reports of their offspring's psychopathology. Method Sixty-five parents with current depression, 42 with current mania/hypomania, 181 with mood disorder in remission, and their offspring (n=479, ages 6-18) completed assessments of offspring IP psychopathology as part of the Pittsburgh Bipolar Offspring Study (BIOS). We compared rates of offspring psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 38 publications
2
45
1
1
Order By: Relevance
“…BRIEF), but not to the performance-based measures of cognition. Consistent with previous studies among non-HIV infected children (Langrock et al, 2002; Maoz et al, 2014), our multivariate analyses showed that depression scores of the caregivers were a significant predictor of the reported behavior scores only for the group of children infected with HIV. All BRIEF indices were significantly associated with caregiver’s depression symptoms, suggesting that is not a particular area of executive functioning but the parent-report as a measure that is associated with the depressive symptomatology.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…BRIEF), but not to the performance-based measures of cognition. Consistent with previous studies among non-HIV infected children (Langrock et al, 2002; Maoz et al, 2014), our multivariate analyses showed that depression scores of the caregivers were a significant predictor of the reported behavior scores only for the group of children infected with HIV. All BRIEF indices were significantly associated with caregiver’s depression symptoms, suggesting that is not a particular area of executive functioning but the parent-report as a measure that is associated with the depressive symptomatology.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest that mothers with depressive symptoms more frequently report behavioral and cognitive problems among their children than non-depressed mothers. Based on parental reports, maternal depression predicted more severe symptom reports among depressed youngsters (Kiss et al, 2007), higher rates of symptoms of depression/anxiety and aggression (Langrock, Compas, Keller, Merchant, & Copeland, 2002), and more externalizing psychopathology (Maoz et al, 2014) in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included maternal demoralization at each follow-up period to control for the potential impact of the mother's psychological state on how she rated her child's behavior (Maoz et al, 2014). If the demoralization measurement was missing at any of the follow-up periods (age 3, n = 2; age 4, n = 3) we imputed a score based on the average of the mother's scores from the two adjacent periods; if two scores were not available, we replaced the missing value with the single score closest in time.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the majority of parent reports are collected from mothers is an important consideration to keep in mind, particularly with regards to depression, as the presence of maternal depressive symptoms is associated with over-reporting of a range of child behavioral problems, including the severity of ASD symptoms (Bennett et al, 2012; Fergusson, Lynskey, & Horwood, 1993; Maoz et al, 2014). Thus, it is possible that depressive symptoms amongst mothers of high-risk infants contribute to the increased frequency of concerns in the first year of life, but this has not been explicitly examined.…”
mentioning
confidence: 99%